Hubungan PHBS (Perilaku Hidup Bersih Sehat) Terhadap Stunting di Desa Kedung Malang Kabupaten Banyumas - Lynawati Lynawati (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
Stunting is a depiction of chronic nutritional status that is chronic in times of growth and development since the beginning of life. Many factors can cause stunting in toddlers such as toddler characteristics or socioeconomic factors. The purpose of this study is to provide understanding and knowledge about stunting to the community and improve clean and healthy living behaviors (PHBS). The factor of low sanitation and environmental hygiene is one indicator of Clean and Healthy Behavior (PHBS). The occurrence of stunting can be caused by several factors. The immediate factor is lack of food intake and the presence of infectious diseases. Infectious disease causes disturbed metabolism of nutrients in the body so that it can cause malnutrition during growth. Other factors are lack of mother's knowledge, wrong parenting, poor sanitation and hygiene and poor health services. The conclusion is that this study suggests that governments, health agencies and related parties collaborate to implement policies to reduce stunting risk. With the socialization of PKK mothers, PKK mothers are expected to receive quality knowledge / education to provide balanced nutrition and improve children's health status.